Review article: does intra-arterial heparin flushing (iahf) can actually increase manual muscle test (mmt) score in chronic ischemic stroke patients? - Machfoed, Moh Hasan; Kurniawan, Mohammad; Usman, Fritz Sumantri (Folia Medica Indonesiana, 2017)
Stroke is still a major health problem in the world. Ischemic stroke accounts for 87% of all acute stroke occurrences. In 2013, the American Heart Association (AHA)/American Stroke Association (ASA), published a Guideline for the Early Management of Patients with Acute Ischemic Stroke. The managements consist of the use of recombinant tissue plasminogen activator (rtPA), endovascular treatment, etc. Unlike acute ischemic stroke, until now, no guidelines have been provided about the management of chronic ischemic stroke that approved universally. The result of the study with the title of "Intra Arterial Heparin Flushing Increases Manual Muscle Test – Medical Research Councils (MMT-MRC) Score in Chronic Ischemic Stroke Patient” is very interesting, because it is a new attempt to treat patients with chronic ischemic stroke. The purpose of this article is to review the study mentioned above, in accordance with the applied scientific principles and is based on the standard literatures and guidelines. Our review is limited only to the discussion of the study results. From this discussion can be proved the existing references that support and/or refuse the study results. Based on the discussions and conclusions of this study, there were no references to support that IAHF can improve motor functions (muscles) in patients with chronic ischemic stroke.